LINK AND MATCH POLICY IN VOCATIONAL EDUCATION TO ADDRESS THE PROBLEM OF UNEMPLOYMENT - AZMIL AZMAN; AMBIYAR; WAKHINUDDIN SIMATUPANG; ARWIZET KARUDIN; OSKAH DAKHI (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2020)
This research is based on the problem of unemployment of educated workers whoare the focus of society. Policies are needed that can increase the relevance of VocationalHigh School to the needs of the world of work, the business world and the industrial world.This research uses qualitative research methods with a case study research approach that aimsto study intensively about the background of the unemployment problem and how linkand match policies can be the solution to the problem of unemployment. The results of thisstudy will provide a broad and in-depth picture of link and match policy, namely with Linkand Match vocational education can know what competencies (skills) the world needs andwhat competencies the world needs most.